IMPLEMENTATION OF GENERATIVE AI AS TOOL FOR MARKETING COMMUNICATION SEMINARS IN UNIVERSITIES - Radek Turčáni (Trendy v podnikání)
Generative AI is reshaping the education landscape, particularly in domains requiring innovation and creativity, such as marketing communication. This paper explores the integration of Generative AI into university-level marketing communication seminars, focusing on its potential as a tool for enhancing learning outcomes and preparing students for real-world challenges. The study evaluates the impact of Generative AI applications like ChatGPT and Gemini on the learning process through a case study approach, identifying benefits, challenges, and key recommendations for effective implementation. The findings suggest that incorporating Generative AI tools into educational frameworks fosters critical thinking and practical skills, essential for contemporary marketing professionals.